Bioinspired Multivalent Peptide Nanotubes for Sialic Acid Targeting and Imaging‐Guided Treatment of Metastatic Melanoma. Issue 22 (24th April 2019) - Lei, Li; Xu, Zhiai; Hu, Xianli; Lai, Yi; Xu, Jie; Hou, Bo; Wang, Ya; Yu, Haijun; Tian, Yang; Zhang, Wen
Abstract: Tumor metastasis is considered a major cause of cancer‐related human mortalities. However, it still remains a formidable challenge in clinics. Herein, a bioinspired multivalent nanoplatform for the highly effective treatment of the metastatic melanoma is reported. The versatile nanoplatform is designed by integrating indocyanine green and a chemotherapeutic drug (7‐ethyl‐10‐hydroxycamptothecin) into phenylboronic acid (PBA)‐functionalized peptide nanotubes (termed as I/S‐PPNTs). I/S‐PPNTs precisely target tumor cells through multivalent interaction between PBA and overexpressed sialic acid on the tumor surface in order to achieve imaging‐guided combination therapy. It is demonstrated that I/S‐PPNTs are efficiently internalized by the B16‐F10 melanoma cells in vitro in a PBA grafting density–dependent manner. It is further shown that I/S‐PPNTs specifically accumulate and deeply penetrate into both the subcutaneous and lung metastatic B16‐F10 melanoma tumors. More importantly, I/S‐PPNT‐mediated combination chemo‐ and photodynamic therapy efficiently eradicates tumor and suppresses the lung metastasis of B16‐F10 melanoma in an immunocompetent C57BL/6 mouse model. The results highlight the promising potential of the multivalent peptide nanotubes for active tumor targeting and imaging‐guided cancer therapy. Abstract : A sialic acid (SA)‐targeted multivalent nanoplatform is presented for chemo‐ and photodynamic therapy of the metastatic melanoma. The nanoplatform is constructed from phenylboronic acid‐grafted peptide nanotubes, which is further loaded with chemotherapeutics and photosensitizer. The nanoplatform can overcome the multiple biological barriers of solid tumors by recognizing SA on the surface of tumor cells for improved cancer therapy.